ANGIOTENSIN I CONVERTING ENZYME INHIBITORY PEPTIDES FROM SWORD BEAN - ZHANG, Y.; CHEN, P.; LIU, L.; LI, K.; WANG, H.; WANG, L. (Italian Journal of Food Science, 2018)
Sword bean is a healthy food and herbal medicine in China. In this study, the main components of sword bean were determined. Albumin, globulin, prolamin and glutelin were hydrolyzed by pepsin and then the angiotensin I converting enzyme (ACE) inhibitory activity was evaluated. Our results showed that glutelin peptides manifested the highest ACE inhibitory activity with inhibitory ratio of 22.10±1.57% followed by prolamin peptides and albumin peptides of 16.77±0.76% and 16.40±0.42%, respectively, at the final concentration of 0.01 mg/mL. Our results strongly suggest that sword bean at some extant have potential to lower blood pressure.